PENYULUHAN KEBERSIHAN LINGKUNGAN: INISIASI GERAKAN SANTRI GO_GREEN - Widiastutie, Sophiana; Setiawan, M. Chairil Akbar; Satrio, Jati; Saraswati, Dini Putri (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Keeping the environment clean is one of the activities that can minimise the harmful effects of natural disasters and damage. If this activity is taught to children, it can form characters, mindsets, and habits to love the environment. The hope is that children will always be able to maintain cleanliness through daily activities, such as disposing of trash in its place and tidying up the room. Because of the importance of instilling awareness always to maintain cleanliness, in this community service, the service team held counselling on the importance of keeping the environment clean for male and female students at Yayasan Al-Kamilah, Serua, Depok, West Java. There are six main stages in implementing this community service: problem identification, problem research, material preparation, event organisation, activity implementation, and activity evaluation. The method used is through lectures, discussions, and demonstrations. In addition, pre-test and post-test were also carried out to find out the understanding of the counselling participants. As a result, the participants understood more about the importance of keeping the environment clean, especially at Yayasan Al-Kamilah, Serua, Depok, West Java.